2019
DOI: 10.3390/ani9050240
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions for Personality Research: Contributing New Insights to the Understanding of Animal Behavior

Abstract: As part of the European Conference on Behavioral Biology 2018, we organized a symposium entitled, “Animal personality: providing new insights into behavior?” The aims of this symposium were to address current research in the personality field, spanning both behavioral ecology and psychology, to highlight the future directions for this research, and to consider whether differential approaches to studying behavior contribute something new to the understanding of animal behavior. In this paper, we discuss the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 160 publications
0
36
0
Order By: Relevance
“…The difference found in the two individuals' responses to olfactory stimuli is a good example of how individuals can respond differently to environmental stress indicating a difference in their personalities. This exhibits how the understanding of different personalities is important in the evaluation of welfare in captive animals [5], implying that different individuals can benefit from different types of enrichment in order to increase their welfare. When exposed to olfactory stimuli, there was a significant difference between the two individuals in the amount of time each spent on stereotypic and inactive behavior, respectively (Appendix B).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The difference found in the two individuals' responses to olfactory stimuli is a good example of how individuals can respond differently to environmental stress indicating a difference in their personalities. This exhibits how the understanding of different personalities is important in the evaluation of welfare in captive animals [5], implying that different individuals can benefit from different types of enrichment in order to increase their welfare. When exposed to olfactory stimuli, there was a significant difference between the two individuals in the amount of time each spent on stereotypic and inactive behavior, respectively (Appendix B).…”
Section: Discussionmentioning
confidence: 99%
“…This can provide researchers with a relatively unbiased evaluation of personality and the effectiveness of enrichment manipulation, which can contribute to the improvement of enrichment programs and animal welfare in captivity [13]. It has been debated whether the study of personality can provide new insights for the field of behavioral ecology [5]. The use of behavioral instability as a new quantitative and systematic method for studying personality could be highly relevant when studying animal conservation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the combination of high variability in spatial behaviour of felids (e.g. dispersal distances of jaguar [82] or lynx [83] and home range size of leopards [84] or lynx [85]) and limited samples common with telemetry-based research [86], suggests the importance of behavioural syndromes could be found if studies had sufficient power [87]. Using different parameterisations, we could evaluate a range of scenarios and identify potential trade-offs between movement behaviour and population level genetic metrics.…”
Section: Limitations Of Our Studymentioning
confidence: 99%